من مظاهـر الالتقـاء بين فكـر عبد القاهر في النظـم وبعـض المبادئ اللغويـة لمدرسة لنـدن (From the joining aspect of Abdul Qahir Aljurjani’s opinion in poetry and a few principles of linguistics schools in London) - (Amer Vaúl Mohammed Balhaf), عامر فائل محمـد بلحاف; (Nasser Omar Mubarak Al-Tamimi), (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث حاول هذا البحث أن يرصد عددًا من مظاهر الالتقاء بين فكر عبد القاهر الجرجاني في النظم وبعض المبادئ التي قامت عليها مدرسة لندن اللسانية، فقسّم الحديث إلى ثلاثة مباحث: الأول بين النظم والقواعد النظامية، والثاني في السياق، وتوقف في الثالث مع مفهوم الرصف. وقد خرج البحث في نهايته بأحد عشر مظهرًا تتلاقى فيها المدرستان، وأرجع هذا الالتقاء إلى الصدفة الفكرية أو ما يُعرف بتوارد الأفكار؛ لأنّ عبد القاهر من جهة، وفيرث وتلاميذه من جهة أخرى يعملون في حقل واحد هو الحقل اللغوي، وفي مجال محدد هو التحليل اللغوي، وكثيرًا ما تؤدي هذه الصدفة إلى نتائج متقاربة في مضمار هذا العلم، لأنّ الباحثين يسلطون الضوء على ظاهرة إنسانية واجتماعية ونفسية واحدة هي اللغة. الكلمات المفتاحية: النظم – القواعد النظامية – السياق – المقام – الرصف Abstract Thisstudy examined a number of aspects of the convergence of Abdul- Qaher Al- Jerjani's thought in meanings of grammar and some of the principles upon which the London School of Linguistic is based on.The study is divided into three sections. The first one deals with meanings of grammar and systemic grammar. The second deals with context, and the third deals with the concept of collocation. The study at the end came up with eleven aspectswhich are similar to the thoughts of the two schools. This similarity is attributed to the intellectual chance or what is known as coincidence, because Abdul-Qaher Al- Jerjani from one hand, and Firth and his fellows on the other hand working in one field which is the field of language, and in a specific area which is linguistic analysis. Often this chance leadsto close results in this field of science, because researchers shed light on one humanitarian, social and psychological phenomenon, which is language. Keywords:Systems - Systematic grammar – Context –Situational Context - Collocations. Abstrak Kajian akan cuba memantau beberapa manifestasi pertemuan antara pemikiran ‘Abdul Qāhir Al Jurjānī dalam teori An Nazm dan beberapa prinsip yang dipegang oleh sekolah linguistik London. Artikel ini terbahagi kepada kepada tiga bahagian iaitu: Pertama, antara teori An Nazm dan sistem nahu umum, kedua, dalam konteks, ketiga, konsep pensejajaran. Menurut kajian terdapat sebelas fenomena pertembungan antara dua aliran pemikiran, pertembungan ini disebabkan oleh persamaan intelektual atau dikenali sebagai pertembungan ide. Ini adalah kerana ‘Abdul Qāhir daripada satu pihak, dan Firth serta pengikutnya daripada satu pihak yang lain mengkaji bidang yang sama iaitu bidang linguistik, atau lebih terperinci bidang analisa bahasa. Kerapkali terjadi akibat pertembungan ini, dapatan-dapatan kajian yang hampir serupa dalam bidang ini kerana para pengkaji menekankan fenomena kemanusiaan, kemasyarakatan serta psikologi yang satu iaitu bahasa. Kata kunci: Teori An Nazm - sistem nahu umum – konteks – situasi – pensejajaran